2007
DOI: 10.1186/1471-2164-8-62
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles in asbestos-exposed epithelial and mesothelial lung cell lines

Abstract: Background: Asbestos has been shown to cause chromosomal damage and DNA aberrations. Exposure to asbestos causes many lung diseases e.g. asbestosis, malignant mesothelioma, and lung cancer, but the disease-related processes are still largely unknown. We exposed the human cell lines A549, Beas-2B and Met5A to crocidolite asbestos and determined time-dependent gene expression profiles by using Affymetrix arrays. The hybridization data was analyzed by using an algorithm specifically designed for clustering of sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 48 publications
3
68
1
Order By: Relevance
“…Gene expression profiling, for example in response to asbestos, is valuable to define early molecular effects as demonstrated in diverse human cells, such as normal human bronchial epithelial cells (NHEC) (45), human lung adenocarcinoma cells (A549) (46,47), SV40-transformed human bronchial epithelial cells (BEAS-2B) and SV40-immortalized pleural mesothelial cells (MET5A) (47). Changes in gene expression are also valuable to determine the pathogenicity pathway of asbestos fibres, as demonstrated in the human mesothelial (LP9/TERT-1) cell line (42).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression profiling, for example in response to asbestos, is valuable to define early molecular effects as demonstrated in diverse human cells, such as normal human bronchial epithelial cells (NHEC) (45), human lung adenocarcinoma cells (A549) (46,47), SV40-transformed human bronchial epithelial cells (BEAS-2B) and SV40-immortalized pleural mesothelial cells (MET5A) (47). Changes in gene expression are also valuable to determine the pathogenicity pathway of asbestos fibres, as demonstrated in the human mesothelial (LP9/TERT-1) cell line (42).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of BCL2, an antiapoptotic/survival gene transcriptionally modulated by CREB, were elevated by asbestos in mesothelial cells, an observation in line with gene expression profiling in crocidolite asbestos-exposed transformed and malignant MM cell lines where increased mRNA levels of BclII/adenovirus E1B 19-kDa interacting protein were reported previously. 37 Up-regulation of the BclII survival pathway by asbestos is one of several survival pathways reported in mesothelial cells exposed to asbestos. 38 -40 Our data also show that MMs have endogenously upregulated BCL2 in comparison with LP9 human mesothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here we used toxicogenomic approaches in human mesothelial cells, a cell type exquisitely sensitive to asbestos (19) and human contact-inhibited ovarian epithelial cells, a cell type not linked to carcinogenesis by asbestos, to determine whether the magnitude of altered gene expression by insoluble particulates correlated with their toxicity to cells and documented pathogenicity in humans. Although a recent study has examined gene expression profiles comparatively in crocidolite asbestos-exposed human lung adenocarcinoma (A549) and SV40-immortalized bronchial (BEAS-2B) or pleural mesothelial cell lines (MET5A) by cluster analysis (20), our studies are the first to examine gene expression changes by asbestos in comparison to other well-characterized particles in a human cell line that exhibits features of normal mesothelial cells (5). Although strict comparisons between cell types are not justified because SV40 Tag was used to immortalize the IOSE ovarian epithelial cell line (6), and SV40 infection is known to decrease sensitivity of human mesothelial cell lines to toxicity by asbestos (21), our studies suggest that the increased numbers of gene expression alterations observed in LP9/TERT-1 human mesothelial cells reflect elevated sensitivity of this cell type to asbestos.…”
Section: Discussionmentioning
confidence: 99%